2011
DOI: 10.1016/j.appet.2011.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Food avoidance in children. The influence of maternal feeding practices and behaviours

Abstract: The aim of this study was to examine the contribution of a broad range of maternal feeding practices in predicting parental reports of food avoidance eating behaviours in young children, after controlling for child temperament, and maternal dietary restraint which have previously been associated with feeding problems. One hundred and four mothers of children aged between 3 and 6 years completed self report measures of their child's eating behaviour and temperament, maternal dietary restraint and child feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
85
0
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 90 publications
13
85
0
15
Order By: Relevance
“…In support of these rather pessimistic hypotheses, higher pressure shows associations with parent reports of lower child enjoyment of food, and higher satiety sensitivity, slowness in eating and food fussiness (Gregory et al, 2010b;McPhie et al, 2011;Webber et al, 2010a), greater child dietary restraint, disinhibited eating, and emotional eating (Carper et al, 2000), greater food avoidance behaviours (Powell et al, 2011), greater neophobia (fear of new foods) and intake of unhealthy snack foods (Brown et al, 2008), and lower fruit and vegetable intake Wardle et al, 2005;Wyse et al, 2011). Johnson & Birch (1994) additionally found that high scores on a general scale of parental control over feeding (e.g. '…”
Section: Pressure To Eatmentioning
confidence: 85%
“…In support of these rather pessimistic hypotheses, higher pressure shows associations with parent reports of lower child enjoyment of food, and higher satiety sensitivity, slowness in eating and food fussiness (Gregory et al, 2010b;McPhie et al, 2011;Webber et al, 2010a), greater child dietary restraint, disinhibited eating, and emotional eating (Carper et al, 2000), greater food avoidance behaviours (Powell et al, 2011), greater neophobia (fear of new foods) and intake of unhealthy snack foods (Brown et al, 2008), and lower fruit and vegetable intake Wardle et al, 2005;Wyse et al, 2011). Johnson & Birch (1994) additionally found that high scores on a general scale of parental control over feeding (e.g. '…”
Section: Pressure To Eatmentioning
confidence: 85%
“…Higher levels of pressure are associated with decreased intake of fruit and vegetable, and increased consumption of low energy-dense foods (fast foods and junk foods during early childhood for both genders) [40]. Furthermore, children who ate unwillingly were more likely to develop avoidant eating behaviors [9,13]. Saudi mothers using such practices could have future implications on children's weight.…”
Section: Discussionmentioning
confidence: 99%
“…Improper feeding practices may impact children's weight status and cause childhood obesity [9][10][11]. Improper feeding practices may endanger children for eating disorders or may lead to overfeeding or underfeeding [12][13][14][15]. For example, preventing children from eating a restricted food can make them consume more of that food, and forcing them to eat can foster a distaste of that food [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Pressure to eat has been associated with increased neophobia (Fisher, Mitchell, Smiciklas-Wright, & Birch, 2002;Wardle et al, 2005; but see Bourcier, Bowen, Meischke, & Moinpour, 2003, for contrary evidence), food avoidance (Powell, Farrow, & Meyer, 2011), decreased liking for and consumption of the to-beeaten food (Galloway et al, 2005;Galloway, Fiorito, Francis, & Birch, 2006) and lower child BMI (in 6-8 year olds, Lee & Keller, 2012;at age 2, Farrow & Blissett, 2008). Indeed, retrospective reports have found that adults' food dislikes can be traced back to negative experiences involving pressure to eat (Batsell, Brown, Ansfield, & Paschall, 2002) and enjoyment of eating is predicted by less pressure to eat (Webber, Cooke, Hill, & Wardle, 2010).…”
Section: Coercive Feeding Practicesmentioning
confidence: 99%